Potensi Antelmintika Ekstrak Bakteri Simbion Spons Laut Terhadap Trichostrongylidae (Nematoda) Parasit Domba - Muhammad Reza Faisal; Mujizat Kawaroe; Fadjar Satrija (Institut Pertanian Bogor, 2016)
Trichostrongylidae (nematodes) parasitic infection of sheep were recently resistance to anthelmintics. Bioactive utilization of bacteria derived sponges had potential as anthelmintics alternative naturally against trichostrongylidae parasitic infections. The Aims of this study was to determine the activity of bacteria derived sponge extracts which produced anthelmintics bioactive compounds against sheep trichostrongylidae parasite. Bacteria derived sponges isolates which labeled S1 and S2 were extracted by methanol. Phytochemical test were conducted to determined characterization of bioactive compounds which potentially to inhibit larvae migration. Concentration which used to Larva Migration Inhibition Assay (LMIA) were 25, 50, 100, 250, and 500 µg/ml. Positive control treatment was used albendazole while negative control by physiological of NaCl. Both of extracts were contained toxicity to againts Artemia salina larvae which <1000 µg/ml concentration. The higher concentration of S1 and S2 extracts were affected to increase larvae migration. Both of extracts were potential to inhibit larvae migration which LC50 value were 165.63 µg/ml (S1) and 374.9 µg/ml (S2). The ability of extracts which inhibit larvae migration caused by bioactive compounds which contained triterpenoids in both of extracts then flavonoid compounds only by S1. Albendazole was showed a highest inhibitory activity which contained 95.5% of the total test nematode larvae.